Teologia moralna - przedmiot dyscypliny naukowej a przedmiot dokumentu. Rozważania z punktu widzenia języka haseł przemiotowych - Szumilas, Dorota (Archiwa, Biblioteki i Muzea Kościelne, 2005)
The article discusses subject cataloguing of the publications in the field of moral theology from the perspective of the science in question, and, more precisely, in view of the subject of moral theology. There is a strict relationship between the subject of the given science and the subjects related and the subject of the publications in the field and this relationship can be noticed in the process of subject cataloguing.